Feature rules in TOPSS tm (Master of Software Engineering, unofficial) - Ingalls, Linda Kay (My University, 2005)
This document describes the development of a new data maintenance tool and the enhancement of a product selection tool at Trane, a subsidiary of American Standard Companies, in LaCrosse, Wisconsin. The product selection tool uses several business rule types that assist a salesman to configure a product. The enhancement adds two new rule types to the existing rule base. The data maintenance tool allows input and maintenance of the two new rule types along with supporting data elements which may be used independent of or in conjunction with the two new rule types. These data items are cached and used as input to the product selection tool.
Keywords: Trane Company; Computer software -- Development; Air conditioning industry -- Equipment and supplies -- Software